Gaya Belajar Mahasiswa Aktivis UIN Raden Mas Said Surakarta - Risda Retno Aji Puspa Utami; Sri Rahmawati Tulit; Umi Latifah (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2021)
This study aims to analyze the learning styles of activist students in maintaining academic values and carrying out their duties as active administrators of the organization, the influencing factors and their impact on the role of student activists. Activist students have three kinds of learning styles, namely visual, auditory, and kinesthetic styles. This study uses a descriptive qualitative approach with case study techniques through interviews, and observations. The informants of this research are the informants of this research, namely student activists at UIN Raden Mas Said Surakarta who specifically have a cum laude IP and become organizational administrators for at least two periods, following at least one organizations. The results showed that the learning styles of student activists at UIN Raden Mas Said Surakarta had several kinds, namely visual, auditory, and kinesthetic styles which were influenced by natural factors. Therefore, it will help student activists in understanding and remembering the information obtained. So, with an appropriate learning style, activist students will still be able to organize.